The spatial rigidity of technological robots - Chupryna, V. M. (НТУ "ХПІ", 2018)
The article considers the actual problem of determining the spatial static rigidity of "one-arc" and "two-handed" technological industrial robots is considered. The method of calculating and constructing the surface of the spatial rigidity of a manufacturing industrial robot with the purpose of further use for determining the accuracy of machining of parts by cutting is developed. It is established that the approach to determining the spatial rigidity of machining machines is common for both robots and machine tools.

Розглянуто актуальну проблему визначення просторової статичної жорсткості технологічних промислових роботів "одношарова" та "дворучна". Розроблено метод обчислення та конструювання поверхні просторової жорсткості виробничого робочого робота з метою подальшого використання для визначення точності механічної обробки деталей за допомогою різання. Встановлено, що підхід до визначення просторової жорсткості обробних верстатів є загальним для обох роботів та верстатів.
Просторова жорсткість технологічних роботів
Keywords: industrial robots; spatial stiffness; static rigidity; industrial robots; elastic system; промислові роботи; просторова жорсткість; статична жорсткість